Ensuring both quality and quantity of EMS. (3rd February 2023) - Richards, Kate
Abstract: In this latest article from the RCVS about the forthcoming changes to its policy on extramural studies (EMS), senior vice president and chair of the RCVS education committee Kate Richards describes how a new balance is being sought between the number of EMS weeks veterinary students are required to undertake and the quality of the placements.